2021
DOI: 10.1192/j.eurpsy.2021.2261
|View full text |Cite
|
Sign up to set email alerts
|

Attention-deficit/hyperactivity disorder as a risk factor for dementia and mild cognitive impairment: A population-based register study

Abstract: BackgroundPrevious research has indicated that attention-deficit/hyperactivity disorder (ADHD) is associated with an increased risk for dementia, but studies are scarce and inconclusive. We aimed to investigate the association between ADHD, and dementia, and mild cognitive impairment (MCI). Additionally, we aimed to investigate the impact of comorbid conditions, educational attainment, head injuries, other developmental disorders, and sex, on the association. MethodsThe study population consisted of 3,591,689 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
27
2
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(35 citation statements)
references
References 37 publications
(135 reference statements)
3
27
2
1
Order By: Relevance
“…Importantly, our study provides unique evidence that higher ADHD-PRS was associated with progressive cognitive decline, predominantly in the memory domain. Since the prototypical clinical phenotype of AD is progressive amnestic symptoms (23), our results support previous epidemiological findings demonstrating that ADHD might be a risk factor for cognitive decline, potentially leading to MCI and dementia syndromes due to AD (68).…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Importantly, our study provides unique evidence that higher ADHD-PRS was associated with progressive cognitive decline, predominantly in the memory domain. Since the prototypical clinical phenotype of AD is progressive amnestic symptoms (23), our results support previous epidemiological findings demonstrating that ADHD might be a risk factor for cognitive decline, potentially leading to MCI and dementia syndromes due to AD (68).…”
Section: Discussionsupporting
confidence: 90%
“…Additionally, cognitive function in older adults with ADHD may closely resemble early manifestations of neurodegenerative conditions (5). Recent population-based large epidemiological studies suggested that ADHD is associated with a higher risk for mild cognitive impairment (MCI) and Alzheimer’s disease (AD) (68). However, these findings rely primarily on electronic health records and consequently can present biased estimates of ADHD and dementia prevalence.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the current paper, we present our hypothesis of the Wnt/mTOR pathway playing a role both in ADHD and sAD pathophysiology, which may explain the recent findings of ADHD as a risk for sAD ( Tzeng et al, 2019 ; Dobrosavljevic et al, 2021 ; Zhang et al, 2022 ). Furthermore, we discuss the possible therapeutic potentials of the psychostimulant methylphenidate (MPH) which, by affecting the Wnt/mTOR pathway, might be beneficial in both disorders.…”
Section: Introductionmentioning
confidence: 85%
“…Attention-deficit/hyperactivity disorder (ADHD) is a heterogeneous neurodevelopmental disorder characterized by impairing levels of inattention, hyperactivity/impulsivity, or both, with an estimated worldwide prevalence of 5-10% in children and 2-5% in adults [1]. The disorder, which frequently co-occurs with other psychiatric and medical conditions [2][3][4][5][6], among others, leads to economic and interpersonal problems, academic impairments, delinquency, and injuries [4,[7][8][9][10] that are associated with a significant individual and healthcare burden [11]. An extensive body of work shows that pharmacologic treatment for ADHD protects against a wide range of adverse outcomes [10] (e.g., injuries and accidents, criminality, substance use disorders, suicide, and traumatic brain injury), at least in the short term.…”
Section: Introductionmentioning
confidence: 99%